Integration of Islamic Values in the Traditional Wedding Customs of the Malay Community in Pekanbaru - Juswandi, Juswandi; Hermansyah, Hermansyah; Nijal, Lasri; Bin Mohd Said, Bambang Suhartono (Lembaga penelitian dan pengabdian kepada Masyarakat, 2023)
This research aims to analyze the Islamic elements present in the traditional wedding customs of the Malay community in Riau. The study adopts a phenomenological case study method to investigate this cultural phenomenon. The findings reveal a strong integration of Malay customs and Islamic values within the Riau Malay culture. The preference for the term